Educational Needs of Students with Hearing Impairment in Enugu State - Chioma Ubah, Josephine; Liziana N. , Onuigbo; Edith O., Ezema; Alison O. P. , Ameh; Chisom Aneke, Chinemerem; David Nnaji, Tochukwu; Mkpoikanke S. , Otu (International Journal of Psychosocial Rehabilitation, 2021)
This study investigated the educational needs of students with hearing impairment in Enugu State, Nigeria. The study adopted a descriptive survey design with six research questions and three research hypotheses tested at 0.05 level of significance. A structured questionnaire titled Hearing Impaired Students Educational Needs Questionnaire` (HISENQ) was developed by the researchers and administered to 30 SS II students with hearing impairment (24 males and 6 females) in Government Secondary School for the Deaf in Qgbete, Enugu state. The data gathered was analyzed using mean and standard deviation for research questions while t-test statistics was used to analyze the hypotheses. The findings were that educational needs of students with hearing impairment in Enugu State include becoming university undergraduates, understanding how to study effectively, and developing good study habits. Also, the findings of this study showed that there is no significant difference between the mean scores of male and female students with hearing impairment in educational needs. Based on the findings, the researchers recommended that governments and school authorities should make provisions for professional guidance counsellors in schools. Also, particular attention should be given to educational needs by the school and that boys and girls should be provided by the same guidance and counselling services irrespective of their sex